«Hijabis» in Spain: their construction as microcelebrities through their YouTube channels - Daniel-David Muñoz-Morcillo; Alejandra Walzer-Moskovic (Communication & Society (Formerly Comunicación y Sociedad))
This article delves into the phenomenon of YouTubers who wear hijab and make it a central identity element in their discourse. Specifically, it addresses the relevance they have within their niche community in Spain, taking into account the socio-cultural factors that enable the visibility of these women as well as the communicative practices they carry out specifically on their YouTube channels. The object of study is the videos produced by these women, their practices in the digital environment and, ultimately, the YouTubers themselves. In the face of ignorance, prejudice and the scant media visibility of positive referents, YouTube becomes a means of expression and visibility for hijabis, promoting dialogue, exchange and identity configuration. A qualitative and quantitative methodology combining content analysis, interview and discourse analysis is used. The corpus of videos analysed is initially N=102, with a subsequent more in-depth analysis on a sample n=20 videos. Muslim hijabis content creators on YouTube play a central role in identity-building dialogues for a community that is often overlooked and lacks positive role models and its own narratives. These women emerge as microcelebrities within their community by creating authentic, intimate, accessible, and frequent content that fosters a deep and affectionate bond with their followers, who progressively develop a sense of identification and connection.